04 Before the fall: a discussion paper on the organisational difficulties of setting up complex randomised control trials in emergency pre-hospital care. Issue 3 (1st March 2011) - Thomas, Gareth; Sanchez, Antonio; Snooks, Helen
Abstract : Aim: To describe unexpected challenges and strategies to overcome them when conducting a randomised control trial (RCT) of a computerised clinical decision support (CCDS) system for the triage of older fallers in emergency pre-hospital care. Background: Few investigations have been conducted in of the emergency pre-hospital care using controlled, randomised, and prospective study designs. A review of 5842 Emergency Medical Services (EMS)-related research articles, published within the past 13 years revealed that fewer than 1% (n=54) were randomised, controlled trials. The paucity of randomised control trials in the pre-hospital care setting is largely due to difficulties in terms of obtaining informed consent, ethical approval, accurate data collection, and actual or perceived resistance to participation in research by busy emergency services. Setting: We are conducting a Department of Health funded RCT (SAFER 1) to evaluate the effectiveness of CCDS which assists ambulance crews to assess and triage older fallers to appropriate care. The trial was planned in three UK ambulance services, in collaboration with local clinicians based within hospitals, primary care and falls services. Study progress: SAFER1 has suffered numerous delays and has had to seek two funding extensions, the latest until 2010. Delays have related to 1) ambulance service reorganisation in England 2) planned and actual (although delayed) implementation of a new electronic patient record in most English services 3) performance pressures 4) internal restructuring of partner services. Discussion: Major modifications of the project timescales and research partners were precipitated by these factors as well as with difficulties in engaging non-research organisations with research protocols, methods and thinking. However, the greatest barriers as well as the greatest facilitation in the implementation of this trial were found to be at the inter-organisational level. We are slowly overcoming these barriers by conducting research that is consistent with corporate administrative systems and by identifying and working closely with key personnel in a flexible way. Our experience leads us to believe that prior to starting a complex trial of this nature, the implementation team should undertake a thorough analysis of the organisational context in which the trial is going taking place. Organisational cultures which are conducive and supportive of research should not be the goal of RCTs, but analysis of organisational and team cultures prior to the trial set up would assist in devising strategies to determine the research process. Clear guidelines for pre hospital care research are urgently needed which encourage this practice.